Pengaruh Suhu dan Lama Pengempaan pada Pembuatan Papan Partikel dari Batang Kelapa Sawit (Elaeis guineensis Jacq.) dengan Perekat Gambir (Uncaria gambir Roxb.) terhadap Sifat Papan Partikel Influence of Temperature and Pressing Time on Particleboard Processing from Palm Oil Trunk (Elaeis guineensis Jacq.) and Gambir (Uncaria gambir Roxb.) Adhesive on Particleboard Properties - Anwar Kasim; Yumarni Yumarni; Ahmad Fuadi (Jurnal Ilmu dan Teknologi Kayu Tropis, 2007)
Studi on the utilization of Palm oil trunk for particleboard with Gambir as adhesive was conducted in order to know the influence of temperature and pressing time to particleboard properties. Experiments were analyzed by factorial with completely randomized design in 4 temperatures (140ºC, 145ºC, 150ºC and 155ºC) and 4 pressing times (10 min., 12.5 min., 15 min., and 17.5 min.). Particleboard was tested for density, moisture content, water absorption, modulus of rupture, compression strength parallel to the surface and internal bond. Result showed that temperature and pressing time and their interaction have significant influenced to the moisture content while pressing temperature have influenced to the density and modulus of rupture of the particleboard. On the other hand, temperature and pressing time have not significant influenced to water absorption, compression strength parallel to the surface and internal bond. The entire particleboard properties were met Indonesian Standard except water absorption which relatively higher. Optimal condition was attained by combination of pressing temperature of 150ºC and pressing time of 15 min., where the density was 0.77g/cm3, moisture content was 7.60%, water absorption was 56.98%, modulus of rupture was 147 kg/cm2, compression strength to the surface was 68.85kg/cm2 and internal bond was 8.26 kg/cm2.